Clostridium tertium:An Unusual Cause of Pyogenic Liver Abscess. Issue 1 (2018) - Barakat, Mohamed; Hernandez, Steven; Benoit, Janeeka; Pourshahid, Seyedmohammad; Mamoon, Yusufal; Martin, George T.
ABSTRACT : N/A: Pyogenic liver abscess (PLA) is the result of portal vein pyemia, which usually originates from the hepatobiliary system or the gastrointestinal tract. Gram‐negative organisms are the most common causative pathogens in PLA. Clostridium tertium is an anaerobic gram‐positive, low‐virulence organism that most commonly affects neutropenic patients with hematological malignancy and has not been reported to cause PLA. We report an unusual presentation of a C. tertium infection as a PLA in a previously healthy, immunocompetent patient with no identifiable source of portal pyemia.